2021
DOI: 10.3390/s21206943
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blue Light on Acne Vulgaris: A Systematic Review

Abstract: Acne is a dermatosis that affects almost 90% of the adolescent population worldwide and its treatment is performed with retinoids, antimicrobials, acids, and topical or systemic antibiotics. Side effects such as skin irritation in addition to microbial resistance to antibiotics are the main side effects found. Phototherapy with blue light is being used as an alternative treatment. Our objective was to analyze the use of blue light to treat inflammatory acne. We conducted a systematic literature review, followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The blue light therapy is suitable for treating acne and killing bacteria on the skin layer. Sadowska et al [5], Diogo et al [6], and Opel et al [7] stated a large number of documented reviews related to the use of blue LEDs phototherapy and they confirmed the conclusive findings that the light from blue LEDs (405-420 nm) was effective in mild to moderate inflammatory of the face treatment of the acne vulgaris and P.acne. In addition, some data [6], [7] indicated that light from the blue LEDs (400-470 nm) may also help treat the acne and P.acne.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The blue light therapy is suitable for treating acne and killing bacteria on the skin layer. Sadowska et al [5], Diogo et al [6], and Opel et al [7] stated a large number of documented reviews related to the use of blue LEDs phototherapy and they confirmed the conclusive findings that the light from blue LEDs (405-420 nm) was effective in mild to moderate inflammatory of the face treatment of the acne vulgaris and P.acne. In addition, some data [6], [7] indicated that light from the blue LEDs (400-470 nm) may also help treat the acne and P.acne.…”
Section: Introductionmentioning
confidence: 84%
“…These parameters should include at least the type of light source, wavelength, optical power, energy, radiation exposure (J/cm 2 ) irradiation or power density (W/m or mW/cm 2 ) and the mode of use of the device (wearable, portable or distance). In this paper, the design goal was set as a power density of red light of 1 0mW/cm 2 and blue light of 20 mW/cm 2 , which was a light intensity suitable for LLLT phototherapy [5], [6], [17], [21] . The authors focused on selecting the LED spectrum to meet the research objectives.…”
Section: -In-1 Led Array Modulementioning
confidence: 99%
“…The mice were anesthetized using 2% isoflurane (MSD Animal Health, Kenilworth, NJ, USA); the mice were placed in the supine position, and the abdomen was irradiated using a blue laser (100 or 30 mW/cm 2 for 20 min). The irradiation conditions were based on those used in clinical practice for PBM using blue light [ 20 , 21 ]. Skin tissues (5 × 5 mm) were collected immediately after irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, light signals are converted into intracellular signals through OPN in human skin photoreception, and this new phototransduction mechanism is of vital importance for understanding photobiomodulation (PBM) therapy, a form of local light therapy based on non-ionizing light sources. Clinically, PBM therapy is becoming a promising treatment for a variety of skin conditions, such as hair regeneration, wound healing, psoriasis, eczema, and atopic dermatitis [135][136][137][138][139]. Future studies focusing on elucidating the underlying mechanisms of different opsins to regulate skin physiological processes, and defining the corresponding light parameters to optimize light therapy will expand clinical indications for PBM and change the treatment landscape for more skin diseases.…”
Section: Phototransductionmentioning
confidence: 99%